2002
DOI: 10.1089/10872910260066688
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Presentations of Primary Human Immunodeficiency Virus Infection

Abstract: Opportunistic infections during primary infection with human immunodeficiency virus (HIV) are rare, with the exception of oral and esophageal candidiasis. HIV-associated nephropathy (HIVAN) and Pneumocystis carinii pneumonia (PCP) typically occur during advanced HIV infection. We report two patients who developed HIVAN and a presumptive diagnosis of PCP, respectively, during primary HIV infection. Serologic testing demonstrated HIV seroconversion. Clinicians need to have a high index of suspicion when evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 11 publications
1
14
1
1
Order By: Relevance
“…Baseline characteristics are summarized in Table 1. Most patients were male (n = 109) with a median age of 32 years (IQR [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. More than half of the patients (53%) defined themselves as men who have sex with men (MSM), while 50 (37%) reported heterosexual exposure.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…Baseline characteristics are summarized in Table 1. Most patients were male (n = 109) with a median age of 32 years (IQR [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. More than half of the patients (53%) defined themselves as men who have sex with men (MSM), while 50 (37%) reported heterosexual exposure.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…10,28 Generally, cerebrospinal fluid (CSF) studies reveal elevated protein, normal glucose and a lymphocytic predominance. 33,37,38 Occasionally, classical opportunistic infections such as Pneumocystis jiroveci pneumonia, histoplasmosis, cryptococcal meningitis, toxoplasmosis, thrush and esophageal candidiasis have been described in the setting of acute HIV infection. Rare central nervous system complications such as encephalopathy, encephalitis, acute disseminated encephalomyelopathy, meningoradiculitis, myelopathy, cauda equina syndrome, coma and myoclonus have also been described.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…A retrospective study of CSF specimens collected in the clinical setting of aseptic meningitis found that 5.3% had HIV RNA detected in the CSF. 24,[38][39][40][41][42][43] These opportunistic infections are the result of transient immunosuppression that occurs during acute infection. 23,[29][30][31][32] Other rare presentations include multiorgan failure, and often, acute HIV infection has been overlooked in these clinical scenarios.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…11,12 Although HIVAN is usually diagnosed late in the course of HIV infection, renal involvement can occur earlier, even during the acute retroviral syndrome prior to HIV antibody seroconversion. 13,14 In a large case series, 20% of symptomatic patients with biopsy-proven HIVAN who required hemodialysis had CD4 lymphocyte counts higher than 200/µL. In a smaller series, 20% of asymptomatic outpatients with biopsy-proven HIVAN who had been screened for proteinuria had CD4 lymphocyte counts higher than 350/µL and 30% had CD4 lymphocyte counts higher than 200/µL.…”
Section: Clinical Featuresmentioning
confidence: 99%